Visualization for Radar Network Detection Ability via Blending Rendering of Multilayer Isosurface - Hu Huaquan; Yang Chao; Wu Lingda (2011 International Conference on Virtual Reality and Visualization, 2011)
Radar network detection performance is described by radar network detection probability. This paper presents two visualization methods of multilayer is surface which is extracted from radar network data for different requirements. The first algorithm, Multilayer Pseudo-sort Algorithm, boosts up the borderline using Per-Pixel Shading, improves the performance of rendering but the quality is low. Another algorithm, Improved Depth Peeling, solves the problem of nonuniform depth distributing of multi-fragment using slice map technology and obtains great improvement for large scenes with high complexity. The former can well balance between performance and quality while the latter can capture multiple fragments in a single process.